The Impact of Phosphorus Supply on Selenium Uptake During Hydroponics Experiment of Winter Wheat (Triticum aestivum) in China - Liu, Hongen; Shi, Zhiwei; Li, Jinfeng; Zhao, Peng; Qin, Shiyu; Nie, Zhaojun (Frontiers in Plant Science, 2018)
Selenium (Se) is a necessary trace element for humans and animals, and Se fertilization is an efficient way to increase Se concentration in the edible part of crops thus enhance the beneficiary effects of Se in human and animal health. Due to the similarity of physical and chemical properties between phosphate (PO43-) and selenite (SeO32-), phosphours (P) supply often significantly impacts the absorption of selenium (Se) in plants, but little is known about how P supply influences the subcellular distribution and chemical forms of Se. In this study, the effects of P supply on subcellular distribution and chemical forms of Se in winter wheat were investigated in a hydroponic trial with medium Se level (0.1 mg Se L-1). Phosphorus was applied with three concentrations (0.31, 3.1 and 31 mg P L-1) in the experiment. The results showed that increasing P supply significantly decreased Se concentration and accumulation in the roots, stems and leaves of winter wheat. An increase in P supply significantly inhibited Se accumulation in the root cell wall, but enhanced Se distribution in the organelles and soluble fraction of toot cells. These findings suggest that increased P supply inhibited the root-to-shoot transport of Se. An increase in P supply enhanced Se accumulation in the stem cell wall and leaf cell organelles, but inhibited Se distribution in the soluble fraction of stems and leaves. This suggests that P supply enhance Se transportation across the cell membrane in shoots of winter wheat. In addition, increased P supply also altered the chemical forms of Se in tissues of winter wheat. These findings will help in understanding of the regulation grain Se accumulation and provide a practical way to enhance Se intake for humans inform Se enriched grains.